Manganese toxicity in rice plants mitigated by silicon effects on leaf tissues - Zanão Júnior, Luiz Antônio; Fontes, Renildes Lúcio Ferreira; Pereira, Jaqueline Dias; Carvalho-Zanão, Maristela Pereira; Pereira, Natalia (Semina: Ciências Agrárias, 2019)
Anatomical modifications of leaves and other organs associated with mineral nutrition have been observed in many plants. However, little is known about the quantitative effects of Si and Mn on the anatomy of plant leaves, especially in rice. This study aimed to quantify the tissue thickness of rice leaves and the density of silica bodies in rice leaves grown in a nutrient solution supplemented with Si and Mn and evaluate the possible effects of Si on Mn toxicity. Treatments were arranged in a 2Ã—3 factorial scheme = six combinations of treatments, two doses of Si (0 and 2 mmol L-1), and three doses of Mn (0.5, 2.5, and 10 Âµmol L-1) in randomized complete block design with four replications. After 39 days in the nutrient solution with the respective treatments, anatomical and micromorphometric measures of the leaf blade were carried out to determine the thickness and area of leaf tissues. The data were submitted to analysis of variance (ANOVA) and Tukey's multiple comparisons test of means(p?0,05). The abaxial and adaxial epidermal thickness, as well as the density of silica bodies increased with the addition of Si to the nutrient solution. This study demonstrated that Si reduced the number of vascular bundles and Mn reduced the thickness of the chlorenchyma with increasing doses. Manganese doses of up to 10 ?mol L-1 do not inhibit the uptake and deposition of silicon in rice leaf tissues. Higher Si concentration in the solution caused anatomical changes in the leaf, which was associated with a possible alleviation of Mn toxicity due to the higher concentration of Si in plants since this effect was observed mainly when Si was present in the nutrient solution.